Analisa Overheating Pada Kompresor Sullair LS16-60/75/100 - Indrawan, Dodi (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2020)
Background The problem faced is overcoming the Overheating of the Screw Air Compressor, the air circulation in the compressor chamber is not good, the Oil has passed the Normal Working Hours, the Oil Separator is clogged, the heat dissipation is blocked in the Coller Unit, the oil filter is clogged with dirt, the Distribution Mechanism in the Oil Filter Housing The unit does not work. Aim of overcoming the overheating that occurs in the compressor which results in a decrease in air pressure on the engine in the production section, knowing the cause of the damage or downtime. Method used is observation of the compressor operation, and checking the compressor engine components. Results and Discussion Overheating on the compressor engine will have an impact on the performance of the engine itself and the air produced. Overheating in the compressor engine is caused by several things including poor air circulation, so the air gets hot and the engine performance decreases. Conclusion minimize damage caused by overheating is to carry out maintenance of the water cooler and oil coller